Practical considerations when inferring lightning current from electric field recordings with a high noise-floor - Lange, Jarren Hilton (My University, 2015)
During a cloud to ground lightning event a charge centre within the storm cloud is discharged. The discharge of a charge centre within the cloud leads to a change in the electric eld radiated by the charge centre. It is theoretically possible to infer the lightning current from the derivative of the electric eld. It is only possible to infer the lightning current from the electric eld data where the noise is comparatively much smaller than the electric eld data. The changing electric elds for a lightning event that occurred on the 3rd January 2015 13:15:13 were recorded by a at plate electric eld sensor with a passive integrator. The oscilloscope used to capture the electric eld data has a relatively large measurement noise and a low resolution. A low pass digital lter was applied to the recorded electric eld data to reduce the e ects from the high frequency noise. The lightning strokes were recorded by the South African Lightning Detection Network. The Lightning Detection Network data is used to obtain the distance of the lightning event from the sensor, to scale the inferred lightning current. The Lightning Detection Network also provides a lightning peak current measurement to compare to the peak current inferred from the electric eld data. The lightning stroke current was inferred from the electric eld recording for various bandwidths of the low pass lter. Inconsistent changes to the inferred lightning stroke current as the lter bandwidth is changed shows that the frequency components for each stroke di ers. The peak stroke current was not constant for any lter bandwidth range implying that the measurement noise is relatively too large. The case study presented demonstrates that with a relatively large noise magnitude (3 to 4 discrete steps of the digital recording) compared to the electric eld signal (21 discrete steps) it is di cult to accurately infer the lightning current from the electric elds recorded.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in ful lment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 2015
Keywords: Lightning--Mathematical models; Electric charge and distribution--Mathematical models; Electromagnetic fields